CLINICAL STUDY ON CS-807 IN RESPIRATORY INFECTIONS - HARADA, TOSHIKAZU; MASHIMO, KEIMEI; YAMANE, YOSHIJI; KATO, TATSUO (CHEMOTHERAPY, 1988)
A new oral cephem antibiotic, CS-807 was administered to 12 patients with respiratory infections, 10 of outpatients and 2 of inpatients. The drug was given a daily dose of 400mg, b. i. d. in 8 patients, 200mg, b. i. d. in 3 patients, and 300mg, t. i. d. in one patient for 5 to 14 days. The clinical result was good in 8 cases and fair in 4 cases. In all cases, normalize of fever, WBC, CRP and ESR, and amelioration of sputum property and decrease of sputum volume were observed in several days after medication. Moreover, in 4 cases with pneumonia marked recovery of chest X-ray findings was found. Bacteriologically, isolates of S. aureus were eradicated in 3 cases and not evaluable in one case, and isolate of H. influenzae was decrease in one case. No side-effect was observed in all cases. Abnormal laboratory values were increase of eosinophile number and slightly elevated GOT, GPT in one case each. None were serious.